Socioeconomic position over the life course from childhood and smoking status in mid-adulthood: results from a 25-year follow-up study - Jing Tian; Seana Gall; Kira Patterson; Petr Otahal; Leigh Blizzard; George Patton; Terry Dwyer; Alison Venn (BMC, 2019)
Abstract Background It remains unclear how life course socioeconomic position (SEP) variations impact later smoking status. We aimed to investigate the associations using a novel methodology - a structured regression framework and to explore the potential underlying mechanisms. Methods Data were from an Australian national cohort (n = 1489). SEP was measured in childhood (aged 7-15 years), young- (aged 26-36 years) and mid-adulthood (aged 31-41 years), including highest parental occupation in childhood and self-occupation in young- and mid-adulthood. Smoking status was self-reported in mid-adulthood. Four smoking-related variables in childhood including exposure to parental smoking, smoking experimentation, self-rated importance to be a non-smoker and intention to smoke were tested as potential mediators. A structured life course modelling approach was used to select the best-fit life course model(s). The log multinomial model was used to estimate the smoking risk in mid-adulthood with never smokers as the excluded category. Results 63.6% of participants were classified as stable non-manual occupation across the life course from childhood. The sensitive period and the accumulation model described the data equally as well as the saturated model. In the sensitive period model, compared to the non-manual group, those who had highest parental occupation of manual had a 21% lower risk of being former smokers and a 32% greater risk of being current smokers in mid-adulthood, and those who were occupied manually in mid-adulthood reported a 55% greater risk of being current smokers in mid-adulthood. In the accumulation model, compared to those who consistently reported non-manual occupations across the life course, those with manual occupations for longer had higher risk of being current smokers in mid-adulthood, with a 43% risk increase per time point in a manual occupation. Exposure to parental smoking and intention to smoke during childhood explained up to 40.2% of the excess risk of being current smokers in mid-adulthood associated with manual occupations in the sensitive period and the accumulation model. Conclusions Childhood, young- and mid-adulthood are all important, but SEP in childhood and mid-adulthood may be of more importance in determining mid-adulthood smoking status. Exposure to parental smoking and intention to smoke in childhood seems to moderately mediate the associations.